Analysis And Synthesis of Dynamic Systems and Transient Processes in The Min Real Automatic Control Systems (Texas Journal of Multidisciplinary Studies, 2021)
In real automatic control systems (ACS), there may be cases when some of the parameters are not known exactly, or they change in during the operation of the system in advance known laws, and their meanings in principle cannot be measurable. If at the same time the ranges of possible values of constants are known parameters or limits of change of unstable parameters, then in such cases one speaks of a pair metric interval uncertainty. Systems having interval indefinite parameters are called interval systems. The following article is devoted to the analysis and synthesis of dynamic systems and transient processes in them in real automatic control systems.